Revision of Marxist Thought in Global Socialist Perspectives - Sharma, Neelam Kumar (Tribhuvan University Journal, 2013)
Marxism gives a common background to both school of thoughts either capitalism or socialism. Marxism is also known as scientific socialism because of its practical validity. Marxism believes that the downfall of capitalism is inevitable according to its own process of dialectic feature. Communism is an extreme limit of Marxism whereas socialism is considered to be a transitional phase of capitalism and communism. The failure of both classical capitalism on the one hand and communism on the other together with the successful achievements of socialism in various countries are sufficient evidences to rationalize the practical validity of socialism in global perspectives. In this context, particularly evolutionary socialists have sufficiently contributed to replace the deficiencies of Marxism in global socialist perspectives.